Historical Audiovisual Fiction in Chile. Continuities and Ruptures (1960-2020) - Antezana, Lorena; Santa Cruz, Eduardo (Revista de Historia Social y de las Mentalidades, 2023)
The main objective of this article is to describe and analyze the historical evolution of the production of works of fiction on Chilean television throughout its history and its relationship with social, political, communicational, and technological contexts. To do this, an attempt is made to unveil a complex process of ruptures and continuities, ranging from black and white and live and direct to current media platforms as well as from mass TV produced in the country that is aimed at national audiences to audiovisual production that has an audience inserted in world markets as a specific segment of that offer.
Keywords: Audiovisual; Fiction; Series; History